Educators in Israel define cultural competence - Shapira, Noa; Shonfeld, Miri; Friedman, Daniela; Falah, Janan Faraj (Frontiers in Education, 2023)
How do Israeli in-service and pre-service teachers perceive the concept of cultural competence? To answer this question, we used a questionnaire survey marking each participant’s degree of agreement with 19 statements defining cultural competency. The questions were open-ended, allowing participants to share their opinions on cultural competence. A quantitative analysis of their responses reveals equal treatment of every person, the ability to receive and provide exact non-injurious messages, cultural awareness, and the ability to communicate in a multicultural environment to be the descriptions most connected to cultural competence. A qualitative analysis discovered several categories of understanding cultural competence, such as knowledge, skills, and values related to the role of teachers in their classrooms. The participants also reflected on Israel’s idiosyncracies and the expectations from educators in such a context. Israeli society is complex and heterogenous: Its education system segregates students, such as through distinct secular, religious, ultraorthodox, and Arabs schools, which, in turn, have their own subcultures, for example. Such layered heterogeneities require an essential understanding of how educators must grasp and define cultural competence in the Israeli educational system.